2006
DOI: 10.1055/s-2006-925027
|View full text |Cite
|
Sign up to set email alerts
|

Recurrence Rate of Anastomotic Biliary Strictures in Patients who have had Previous Successful Endoscopic Therapy for Anastomotic Narrowing after Orthotopic Liver Transplantation

Abstract: Biliary strictures remain a common complication after OLT, and in nearly one in five patients these strictures recur after initially successful endoscopic therapy. There were no clinical or endoscopic parameters identified in this study that predicted recurrence. Further study is needed to determine what type of endoscopic therapy would minimize the risk of stricture recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
52
2
12

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(68 citation statements)
references
References 6 publications
2
52
2
12
Order By: Relevance
“…An increasing number of stents can be used at each session to achieve a maximum diameter. The majority of patients require several endoscopic interventions, with a mean of 3 to 5 with long term success rates in the range of 70%-100% [3,32,36,37,68,69,[71][72][73][74] . A protocol of accelerated dilation every 2 wk, and a shortened stenting period of an average of 3.6 mo, showed some encouraging results with a high 87% success rate [68] .…”
Section: Diagnosismentioning
confidence: 99%
“…An increasing number of stents can be used at each session to achieve a maximum diameter. The majority of patients require several endoscopic interventions, with a mean of 3 to 5 with long term success rates in the range of 70%-100% [3,32,36,37,68,69,[71][72][73][74] . A protocol of accelerated dilation every 2 wk, and a shortened stenting period of an average of 3.6 mo, showed some encouraging results with a high 87% success rate [68] .…”
Section: Diagnosismentioning
confidence: 99%
“…Significantly, more recurrences were seen in the patients who developed AS after more than 6 months after orthotopic liver transplantation compared to those with AS in the first 6 months . Recurrence rate of post-anastomotic biliary strictures was reported by Alzami et al to be relatively small (18%) over a follow-up period of almost 3 years (Alazmi et al, 2006), while others reported to be around 10%-13% (Morelli et al, 2003). They concluded that recurrence could be effectively diagnosed and treated by endosopic approach requiring between one and four additional sessions.…”
Section: Deceased Donor Liver Transplantation (Ddlt)mentioning
confidence: 93%
“…Factors found to be associated with poor outcome and/or higher recurrence following endoscopic treatment or stent removal include delayed initial presentation (more than 6 months after transplantation), presence of tight strictures (Alazmi et al, 2006;Verdonk et al, 2007), presence of bile leaks, and use of T tubes (Sharma et al, 2008;Alazmi et al, 2006). The conventional method of endoscopic treatment comprises of stricture localization followed by guidewire cannulation, balloon dilatation, and subsequent placement of plastic stents.…”
Section: Deceased Donor Liver Transplantation (Ddlt)mentioning
confidence: 99%
See 1 more Smart Citation
“…They tend to occur earlier than AS with mean time of presentation 3-6 mo post-LT and have an incidence of 5%-15% [23,24] . Although most NAS are multifactorial, to hepatic artery thrombosis (HAT) leading to biliary destruction; (2) microangiopathic -secondary to they can further be divided into 3 sub-types based on their etiology: (1) macroangiopathic -secondary studies for DDLT [32,[35][36][37][38] but decreases to 37%-71% in patients with LDLT [39,40] because of the more complex duct-to-duct anastomosis. Factors limiting efficacy include peripheral location and presence of smaller and multiple biliary anastomotic strictures.…”
Section: Biliary Stricturesmentioning
confidence: 99%